Towards the Application of Atorvastatin to Intensify Proapoptotic Potential of Conventional Antileukemic Agents In Vitro - Jolanta D. Żołnierczyk; Arleta Kaźmierczuk; Paweł Hikisz; Barbara Cebula-Obrzut; Ewa Wawrzyniak; Jerzy Z. Błoński; Małgorzata Misiewicz; Paweł Robak; Piotr Smolewski; Zofia M. Kiliańska (Journal of Chemistry)
It has been previously revealed that statins used at high concentrations display antileukemic potential towards chronic lymphocytic leukemia (CLL) cells. However, their usage alone in clinical practice may be limited due to possible side effects of high doses of these drugs. On the other hand, combined treatment of leukemia with statins and the conventional chemotherapeutics is questionable because of unknown influence of the first on the standard treatment results. This study has revealed that in vitro atorvastatin increases the proapoptotic potential of cladribine and mafosfamide in CLL cells isolated from peripheral blood of patients. Moreover, a preincubation with the above statin sensitizes leukemic cells to CM-induced apoptosis even at small concentrations of the drug. The usage of atorvastatin together with or followed by the conventional chemotherapy should be considered as therapeutic option for the treatment for this leukemia. Interestingly, CM-resistant patients might have the biggest benefits from atorvastatin administration.